Analisis Pengaruh Rasio Keuangan Dan Ukuran Perusahaan Terhadap Return Saham (Studi Empiris pada Perusahaan Sektor Properti dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2011-2014) - Novitasari, Dewi Musthofa; , Drs. Eko Sugiyanto M.Si (2017)
This study aimed to analyze the influence of Current ratio (CR), Debt to Equity Ratio (DER), Return on Assets (ROA), Inventory Turnover (ITO), Earning per Share (EPS) and the size of the company to return stock at property and real estate sector companies listed in BEI 2011-2014 period.This study used 44 samplesof property and real estate sector companies from 2011-2014 listed in the BEI. Samples were selected by using purposive sampling method. The data used were secondary data. Analysis of data used descriptive statistics, classical assumption test and multiple regression analysis. Variables used in this research were the Current ratio, Debt to Equity Ratio, Return on Assets, Inventory Turnover, Earning per Share and the size of the company as an independent variable; the stock return as the dependent variable. The results of this study indicated that the current ratio, Debt to Equity Ratio, Inventory Turnover, Earning per Share and the size of the company do not have a significant effect on stock returns. Meanwhile, variable Return on Assets significantly affects stock returns.